2006
DOI: 10.1007/s00586-005-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

Anterior dual rod instrumentation in idiopathic thoracic scoliosis

Abstract: For anterior correction and instrumentation of thoracic curves single rod techniques are widely used. Disadvantages of this technique include screw pullouts, rod fractures and limited control of kyphosis. This is a prospective study of 23 consecutive patients with idiopathic thoracic scoliosis treated with a new anterior dual rod system. Aim of the study was to evaluate the safety and efficacy of this new technique in the surgical treatment of idiopathic thoracic scoliosis. To the best knowledge of the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
7

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 32 publications
0
26
0
7
Order By: Relevance
“…Most reports on the anterior thoracic instrumentation used end-to-end fusions, in which length of the fusion was the same as the curve length [2, 4-6, 9, 11, 14]. Liljenqvist et al [14] reported anterior fusion with dual rod instrumentation and end-to-end fusions, with a thoracic curve correction of 57.5%. Brodner et al [15] reported on short fusions using dual rod instrumentation in single thoracic curves but the prospective pulmonary function results were not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports on the anterior thoracic instrumentation used end-to-end fusions, in which length of the fusion was the same as the curve length [2, 4-6, 9, 11, 14]. Liljenqvist et al [14] reported anterior fusion with dual rod instrumentation and end-to-end fusions, with a thoracic curve correction of 57.5%. Brodner et al [15] reported on short fusions using dual rod instrumentation in single thoracic curves but the prospective pulmonary function results were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudarthrosis and implant failures were also reported [11,12]. The length of standard thoracotomy exposure, the length of spinal fusion and the bulk of anterior implants may be contributing factors for the postoperative reduction of pulmonary function [13,14]. We used a mini-thoracotomy incision for exposure and low-profile implants for the instrumentation of the thoracic spine.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [33], our group documented a kyphogenic trend when an anterior dual rod instrumentation system was used to treat thoracic scoliosis in 23 patients. The better restoration provided by anterior dual rod instrumentation is probably due to using a second solid rod, allowing individual contour adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Die Vorteile insbesondere der ventralen Derotationsspondylodese nach Zielke sind die kurze Fusionsstrecke und die gute Derotation und Korrektur in der frontalen Ebene. Die Nachteile der fehlenden Primärstabilität sowie der mangelnden Kontrolle des sagittalen Profils konnten im Rahmen von Weiterentwicklungen eliminiert werden [9]. …”
Section: Ventrale Instrumentationsspondylodesenunclassified